The Local Cultural Text Of L.Solovyov's Novel "The Tale Of Khoja Nasreddin" (Texas Journal of Philology, Culture and History, 2024)
In this article is considered the structure of the artistic space in modern literature and also take an important place such notion, as “urban text”, which have its own history of origin and development.